Revitalizing Indigenous Women’s Water Governance Roles in Impact and Benefit Agreement Processes Through Indigenous Legal Orders and Water Stories - Hania, Patricia (Les Cahiers de droit, 2019)
In the Canadian mining sector, the use of an impact and benefit agreement (IBA) is the dominant legal instrument that structures the legal relationship between a First Nation and a proponent. However, barriers to Indigenous women’s participation in IBA law-making exist, which raises the question : How can IBA law-making be strengthen to include Indigenous women ? Emergent scholarship by Graben, Cameron and Morales takes up this question of Indigenous women’s participation in their gendered approach. In this article, I critically examine and expand upon Graben, Cameron and Morales gendered approach, and argue that mining, Indigenous women, and water are interconnected, and advancing Indigenous women’s participation is essential, as argued by Graben, Cameron and Morales. However, offering Indigenous women a place at the IBA negotiating table is meaningless without recognizing their Indigenous law stories and governance responsibilities to speak for water, as long argued by Indigenous water governance scholars and Indigenous women.